Trajectories and Interactions of Dyadic Coping and Depression in Patients After Thrombolysis for Acute Ischemic stroke: A Longitudinal Study in China - Liu J; Xu L; Li XQ; Chen D; Ji KX; Qiu LF (Psychology Research and Behavior Management)
Jingxiu Liu,* Lei Xu,* Xiao-qin Li,* Dandan Chen, Kang-xiang Ji, Lan-feng Qiu Department of Emergency Medicine, The First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, 215009, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lan-feng Qiu, Department of Emergency Medicine, The First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, 215009, People’s Republic of China, Email 15062100130@163.comObjective: To explore the developmental trajectory of dyadic coping and depression in stroke patients and the predictive relationship between the two and to provide a theoretical basis for improving depression in stroke patients.Design: A longitudinal study.Methods: Two hundred and forty-two stroke patients who underwent thrombolysis in the emergency department of our hospital from January 2023 to March 2024 were selected as the study subjects, and their dyadic coping and depression were tracked and investigated in T1 (after thrombolysis), T2 (3 months after the disease), and T3 (6 months after the disease), and the data were analyzed using a cross-lagged model and latent variable growth model.Results: Two hundred and twelve valid serial questionnaires were recovered at the completion of the three time points. Stroke patients showed an increasing trend in dyadic coping and a decreasing trend in depression. Pearson correlation showed that the correlation between the two was significant at all 3 time nodes (P< 0.05). Cross-lagged modeling showed that dyadic coping levels on average significantly and positively predicted depression at the next node, whereas depression did not significantly predict dyadic coping longitudinally at the next node. The latent variable growth model showed that dyadic coping (S=3.215, P< 0.001) tended to increase and depression (S=− 0.292, P< 0.001) tended to decrease from T1 to T3 in stroke patients; at the initial level, dyadic coping was negatively correlated with depression (r=− 0.356, P=0.002), initial levels of dyadic coping were able to positively predict itself (β=0.355, P=0.007) and the rate of development of depression (β=0.515, P=0.002), and the rate of development of dyadic coping was able to positively predict the rate of development of depression (β=0.584, P< 0.001).Conclusion: Dyadic coping was negatively associated with post-stroke depression, suggesting that higher levels of dyadic coping may serve as a protective factor against depressive symptoms in stroke survivors. This relationship underscores the potential therapeutic value of fostering mutual support and adaptive problem-solving strategies within patient-caregiver dyads, highlighting the clinical importance of integrating dyadic coping interventions into post-stroke mental health care.Keywords: stroke, thrombolysis, dyadic coping, depression, trajectory, interaction relationship, longitudinal study, correlation